A case of Triploidy - Nur Syahrina Binti Rahim; Teresa Chow; Abd Rahman Hayati (College of Pathology, 2024)
Introduction: Triploidy is one of the commonest chromosomal aberrations in first trimester spontaneous miscarriages. We describe a case of Triploidy Syndrome diagnosed in the second trimester. Case report: A 32-year-old lady in her second pregnancy at 15 weeks gestation was noted to have oligohydramnios and a fetus that was small for gestational age. Detailed ultrasound showed a male fetus with several abnormalities which include micrognathia, frontal bossing, bilateral mild ventriculomegaly, clawed hands, bilateral talipes, constricted chest, small stomach and a small bladder. At 19 weeks an intrauterine death was confirmed. At autopsy the fetus was macerated and the parameters corresponded to a 16-week-old gestation. Additional features noted were hypertelorism, microphthalmia, malformed low set ears, small mouth, short nasion and micropenis. The limbs abnormalities include bilateral syndactyly of third and fourth fingers, syndactyly of third and fourth digits of right foot, rocker bottom feet and bilateral talipes equinovarus. There was hypoplasia of the right lower limb with thinning at the middle anterior part of the thigh. On internal examination there were hypoplastic alobar lungs, stenosed ductus arteriosus, pulmonary trunk hypoplasia and adrenal hypoplasia. The placenta showed no evidence of hydatidiform mole. Fetal DNA analysis following amniocentesis revealed a Triploidy Syndrome containing XXY chromosome. Discussion & conclusion: Triplody can be classified into diandric or digynic types. The former reflects extra haploid set of chromosomes of paternal origin and associated with partial hydatidiform mole. The digynic type represents extra haploid set of maternal origin and is more likely to live into second trimester which was demonstrated in our case.